Pengaruh Media Manik-manik Warna Terhadap Keterampilan Berhitung Siswa Kelas 1 SD - Ahsanidiawati, Nenden Sri; Yuliati, Yuyu (Papanda Publisher, 2023)
One of the reasons for the low numeracy skills in elementary schools is the lack of application of instructional media which provides opportunities for students to practice directly and train themselves to be skilled at counting. To improve students' numeracy skills, learning innovations are needed that involve students actively through direct learning experiences. One alternative solution to this problem is to use colored beads as learning media in learning Mathematics in Elementary Schools. This study aims to find out 1) to know the application of color bead media to grade 1 elementary school mathematics 2) to find out the increase in math skills in grade 1 elementary school students after using color bead media, and 3) to know the effect of using the media the color of the beads on the numeracy skills of 1st grade students. This research is a systematic literature study. Based on this discussion, the media of colored beads is very effective for improving students' numeracy skills, because students have the opportunity to directly practice and train themselves to be skilled at counting. The results of the research are expected to provide an overview for developing further research regarding improving numeracy skills through learning media of colored beads in mathematics in elementary schools.